2015
DOI: 10.1016/j.neulet.2015.06.039
|View full text |Cite
|
Sign up to set email alerts
|

MIR137HG risk variant rs1625579 genotype is related to corpus callosum volume in schizophrenia

Abstract: Genome-wide association studies implicate the MIR137HG risk variant rs1625579 (MIR137HGrv) within the host gene for microRNA-137 as a potential regulator of schizophrenia susceptibility. We examined the influence of MIR137HGrv genotype on 17 subcortical and callosal volumes in a large sample of individuals with schizophrenia and healthy controls (n=841). Although the volumes were overall reduced relative to healthy controls, for individuals with schizophrenia the homozygous MIR137HGrv risk genotype was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…When traumatic childhood attachment experiences remain unresolved it may account for reduced white matter integrity of the splenium, but abnormalities of the genu and body of the corpus callosum may be the consequence of a general vulnerability for psychopathology that might be a result of genetic influences [60] or prenatal stress [61]. Our findings indicated that the smaller FA values in the genu and body were due to increases in AD, RD, and MD.…”
Section: Accepted Manuscriptmentioning
confidence: 65%
“…When traumatic childhood attachment experiences remain unresolved it may account for reduced white matter integrity of the splenium, but abnormalities of the genu and body of the corpus callosum may be the consequence of a general vulnerability for psychopathology that might be a result of genetic influences [60] or prenatal stress [61]. Our findings indicated that the smaller FA values in the genu and body were due to increases in AD, RD, and MD.…”
Section: Accepted Manuscriptmentioning
confidence: 65%
“…As ventricle size and total brain volume are inversely correlated (Horga et al, ), this increased ventricular volume association may be comparable to the link between decreased total brain volume and PRS in the present study. A final structural MRI study reported by Patel et al () examined the effect of rs1625579 genotype on subcortical and callosal volumes and reported evidence of an association between the risk (G) allele and decreased corpus callosum volume in SZ patients only ( n = 362) compared to controls ( n = 490). We did not examine this measure in our sample, although potentially a decrease in corpus callosum volume may contribute to the decrease in overall brain volume reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we previously observed an association between a MIR137 PRS and memory scores, and between MIR137 PRS and altered neural connectivity during performance of a fMRI working memory task (Cosgrove et al, ). There are conflicting reports of the effect of the rs1625579 SNP on brain volume (Cousijn et al, ; Lett et al, ; Patel et al, ; Rose et al, ); however, to date, the effect of an empirically derived miR‐137 regulated gene score on structural brain measures has not been established. Such investigations into potential associations between genetic pathways and brain‐based correlates of cognitive phenotypes may assist in elucidating pathophysiological mechanisms that act as contributing factors to these cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…The rs1625579 T allele was linked to a significant regional effect by decreasing the expression of miRNA-137 and increasing the risk of Sz in nine brain regions. Therefore, the TT genotype was correlated with greater regional volume compared with that of the GG/GT genotype in Sz patients (72,73).…”
Section: Mechanism Of Rs1625579mentioning
confidence: 88%
“…The rs1625579 T allele was linked to a significant regional effect by decreasing the expression of miRNA‐137 and increasing the risk of Sz in nine brain regions. Therefore, the TT genotype was correlated with greater regional volume compared with that of the GG / GT genotype in Sz patients . In addition, other studies confirmed that miRNA‐137 expression was not only regulated by the rs1625579 genotype but was also influenced by the environment, a phenomenon known as ‘gene × environment’ interactions .…”
Section: Mirna‐137mentioning
confidence: 89%